Financial Ratio Analysis As An Instrument For Evaluating The Financial Performance Of The Padang City Drinking Air Resources In Optimizing Fund Management - Umniati Khairunnisa; Nur Aliah; Dwi Saraswati (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to evaluate the financial performance of Perumda Air Minum Kota Padang through financial ratio analysis as an instrument to optimize the company's fund management. Using a descriptive quantitative approach, this research analyzes financial report data from 2022 to 2024, focusing on liquidity, solvency, profitability, activity, and operational ratios based on the standards of the Minister of Home Affairs Decree Number 47 of 1999. The results indicate that the company's financial performance falls into the